Growth of Gliricidia and Leucaena as affected by Rhizobium inoculation and N and P fertilizar application in Nigeria - Onafeko, O.; Kang, B.; Omueti, J.A. (1995)
Six field trials to determine the effects of rhizobium inoculation, and N and P fertilizer applications on the early growth of Gliricidia sepium and Leucaena leucocephala were conducted in farmers' fields at three sites: Alabata and Ajaawa located in the derived savanna of southwestern Nigeria and Zakibiam located in the southern Guinea zone of ease central Nigeria. At Alabara and Ajaawa the soils are Entisols and mean annual rainfall was 1300 mm; at Zakibiam, the soils belonged to the Alfisol group with a mean annual rainfall of 1070 mm. By 15 MAP Gliricidia responded significantly to inoculation in four fields and to fertilization in two fields. Leucaena responded significantly to inoculation in three fields and to fertilizer application in one field. The performance of the two species was better at Alabata and Ajaawa than at Zakibiam. The better performance may be related to soil fertility and rainfall. Gliricidia showed better early growth than Leucaena. The faster growing Gliricidia responded better to inoculation and fertilization. The mean response to rhizobium inoculation was higher in the control than in plots fertilized with N. The N response was more pronounced than P response in spite of the low available P level of the fields. Inoculation, and N and P fertilization increased the N and P uptake of the two species. To ensure the early establishment of both species, inoculation with rhizobium and starter applications of N and P fertilizers is highly recommended.